2010
DOI: 10.1002/pro.367
|View full text |Cite
|
Sign up to set email alerts
|

CTCF terminal segments are unstructured

Abstract: The human CCCTC-binding factor, CTCF, organizes and regulates transcription of the genome by colocalizing distant DNA elements on the same and even different chromosomes. This protein consists of 11 zinc fingers flanked by polypeptide segments of unknown structure and function. We purified recombinant terminal fragments and observed that both are extended, monomeric, and predominantly consist of unordered content. We thus speculate that the role of the terminal extensions, and perhaps all of CTCF, is to act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…Despite their critical role in 3D genome organization, we know surprisingly little mechanistically about CTCF and cohesin. The function of CTCF's largely unstructured N-and C-terminal domains remain largely unknown (Martinez and Miranda, 2010;Merkenschlager and Nora, 2016). Similarly, although the related SMC-complex condensin has been observed to extrude loops in vitro (Ganji et al, 2018), in vitro singlemolecule studies of cohesin failed to detect extrusion (Davidson et al, 2016;Kanke et al, 2016;Stigler et al, 2016).…”
Section: How Do Ctcf and Cohesin Interact?mentioning
confidence: 99%
“…Despite their critical role in 3D genome organization, we know surprisingly little mechanistically about CTCF and cohesin. The function of CTCF's largely unstructured N-and C-terminal domains remain largely unknown (Martinez and Miranda, 2010;Merkenschlager and Nora, 2016). Similarly, although the related SMC-complex condensin has been observed to extrude loops in vitro (Ganji et al, 2018), in vitro singlemolecule studies of cohesin failed to detect extrusion (Davidson et al, 2016;Kanke et al, 2016;Stigler et al, 2016).…”
Section: How Do Ctcf and Cohesin Interact?mentioning
confidence: 99%
“…CTCF is an 11-zinc finger (ZF) protein flanked by unstructured N-and C-terminal polypeptides, containing ;727 amino acids and two transcription repressor domains, with flexible binding to divergent regulatory DNA sequences [28][29][30]. CTCF domains are highly conserved among vertebrates [31,32], consistent with an essential role for CTCF in cellular function [27].…”
Section: Ctcf Structure and Functionmentioning
confidence: 99%
“…18 One of the most interesting examples in eukaryotes is the CCCTC binding factor, known as CTCF, which is responsible for regulation of chromatin architecture by forming chromatin loops and co-localizing spatially separated DNA segments. 19 With more than 77,000 identified binding sites on the eukaryotic genome, CTCF plays a critical role in transcriptional regulation, both in promoting and in repressing the expression of We hypothesize that in protein networks with random topologies, the effect of transcriptional noise on protein interactions would be significantly buffered due to the absence of hub proteins. However, studies on protein networks have shown that rarely are these networks randomly organized.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, much of CTCF functional versatility is attributed to the disordered polypeptide segments that form more than half of its amino acid sequence and are thought to function as scaffolds for protein assembly in transcriptional regulation. 19 Given that most chromatin remodelers and transcriptional factors are IDPs, 18,21,22 it is conceivable that transcriptional noise in these IDP hubs will directly contribute to the total transcriptional noise of the system. This hypothesis is partly supported by recent evidence suggesting that the percentage of disordered regions is an important determinant of dosage sensitivity among proteins.…”
Section: Introductionmentioning
confidence: 99%